Design, Synthesis, Biological Activity, and Structural Analysis of Lactam‐Constrained PTPRJ Agonist Peptides. (4th July 2018) - Sala, Marina; Spensiero, Antonia; Scala, Maria Carmina; Pepe, Giacomo; Bilotta, Anna; Paduano, Francesco; D'Agostino, Sabrina; Lanzillotta, Delia; Bertamino, Alessia; Novellino, Ettore; Trapasso, Francesco; Gomez‐Monterrey, Isabel M.; et al.
Abstract: PTPRJ is a receptor‐like protein tyrosine phosphatase mainly known for its antiproliferative and tumor‐suppressive functions. PTPRJ dephosphorylates several growth factors and their receptors, negatively regulating cell proliferation and migration. We recently identified a disulfide‐bridged nonapeptide, namedPTPRJ‐19 (H‐[Cys‐His‐His‐Asn‐Leu‐Thr‐His‐Ala‐Cys]‐OH), which activates PTPRJ, thereby causing cell growth inhibition and apoptosis of both cancer and endothelial cells. With the aim of replacing the disulfide bridge by a chemically more stable moiety, we have synthesized and tested a series of lactam analogues ofPTPRJ‐19 . This replacement led to analogues with higher activity and greater stability than the parent peptide. Abstract : Disulfide vs. lactam : This work focused on the design and biological evaluation of PTPRJ agonist peptides. Derivatives ofPTPRJ‐19 were generated by replacing the disulfide bridge chain with a lactam bridge. Our study provided a new derivative, peptide7, with better anticancer cell growth activity and improved stability under various conditions.